Effects of sweet potato (Ipomea batatas) vines inclusion to napier grass (Pennisetum purpureum) on the chemical composition and physical properties of silage mixtures - S., Jusoh; M.Y., Martini; B., Safwah Najihah (Malaysian Society of Animal Production, 2023)
Napier grass (Pennisetum purpureum) is renowned for its high yield as forage and is primarily cultivated by small-scale farmers to nourish their livestock. When harvested at the recommended age, it can offer premium-quality feed. Conversely, sweet potato vines (SPV) are often treated as agricultural residue due to being underutilized, despite their potential nutritional benefits. This disregard for Sweet Potato vines stems from a lack of interest in further processing them into feed. This study aimed to assess the chemical composition and physical attributes of ensiled napier grass mixed with different proportions of Sweet Potato vines for 30 days. The experimental groups included 100% NG, 75% NG:25% SPV, 50% NG:50% SPV, 25% NG:75% SPV, and 100% SPV. The research utilized ordinary Napier grass and Bukit Naga Sweet Potato vines, both harvested at 6 weeks old during the second harvesting cycle. The quality of silage was evaluated through physical characteristics such as colour and pH. All treatments displayed optimal pH levels for quality silage, falling within the range of 3.5 to 4.0. The colour assessment indicated that all treatments had a greenish-brown hue with a discernible structure. Chemical composition analysis was performed using proximate analysis procedures. In conclusion, incorporating SPV elevated OM and CP content, demonstrating the potential benefits of combined ensiling.